Design Piracy in the Fashion Industries of Paris and New York in the Interwar Years - Pouillard, Véronique (Business History Review, 2011)
During the Great Depression, counterfeiters of the newest styles posed a challenge to the high-fashion designers who dominated Parisian design. Meanwhile, New York, traditionally the destination of the first corporate buyers of Paris couture, became a potential contender for the role of fashion capital. Scrutiny of French and American laws reveals that strong national interests were at stake in the fashion business. In France, the law safeguarded copyrights of fashion design while, in the United States, legislators denied such protection to American fashion.
Keywords: Business History and gender